O surgimento das práticas de assistência à saúde mental da criança inspiradas na psicanálise no início do século XX através da obra de Durval Bellegard Marcondes - Abrão, Jorge Luís Ferreira [UNESP] (My University, 2014)
Psychoanalysis was introduced in Brazil since 1920 contributing to the appearance of new practices of health care for the child. Therefore, the present article aims to discuss the link between psychoanalysis and practices focused on children's mental health that emerged from the 1930s through the work of Durval Marcondes, a pioneer in the dissemination and use of psychoanalysis in Brazil. A historical research was held from a survey on Durval Marcondes’s work and the team led by him confined in the epigraph theme. It was found from that work that the link between mental hygiene, new school and psychoanalysis developed a pioneering service of care to children with school problems based on the diagnostic evaluation and guidance of parents and teachers. It is concluded that this work introduced the differentiation between children with cognitive and emotional problems and provided the foundations of psychoeducational and psycodiagnostic interventions.

A psicanálise foi introduzida no Brasil a partir de 1920 contribuindo para o surgimento de novas práticas de atenção à saúde da criança. Assim, o presente artigo tem por objetivo discutir a articulação entre a psicanálise e as práticas voltadas à saúde mental da criança surgidas a partir de 1930 por intermédio da obra de Durval Marcondes, pioneiro na difusão e utilização na psicanálise no Brasil. Foi realizada uma pesquisa histórica a partir de levantamento da obra de Durval Marcondes e da equipe por ele liderada circunscrita no tema em epigrafe. A partir deste material identificou-se que a partir da articulação entre higiene mental, escola nova e psicanálise, desenvolveu-se um serviço pioneiro de atendimento à crianças com problemas escolares sustentado na avaliação diagnóstica e na orientação de pais e professores. Conclui-se que este trabalho introduziu a diferenciação entre criança com déficit cognitivo e problemas emocionais e lançou as bases das intervenções psicodiagnóstica e psicopedagógica.
The emergence of the practice of mental health care of children inspired by psychoanalysis in the early twentieth century through the work of Durval Bellegarde Marcondes
Keywords: Psychoanalysis; Child; Mental health; Psicanálise; Criança; Saúde mental